Inconstitucionalidad del art. 68.1 de la Ley Orgánica de Justicia Laboral en relación a la eliminación del aporte estatal del 40% al instituto ecuatoriano de seguridad social (IESS) para las pensiones jubilares - Alvarado Tanguila, Cesar Pablo (2015)
On April 20, 2015 and published in the Official Gazette, Third Supplement, No. 483, went on to integrate and complement regulation in labor matters in Ecuador Organic Labor Law of Justice and Labor Award in the Home, the same which amends the Social Security Act and other regulatory bodies such as the labor code, the law of public enterprises and the organic law of public service. Among the main points, the rules in question establishes some regulations addressed to forewarn the rights of members and allow protection and protection of the recipients or beneficiaries of certain rights of social security. With this reform, which is inserted into the Social Security Act, his art is practically unknown. 237 for the state contribution of 40 percent for retirement pensions and health care; also disregarded payment agreements signed in several stages by government officials and finally breached the report of the Comptroller General whereby state commitments to the IESS was determined. Against the background described, the elimination of state contribution of 40% of the Ecuadorian Social Security Institute (IESS) for retirement pensions, as well as being clearly unconstitutional, violates several international treaties; you can not skip described in Art. 11 of the Constitution of the Republic to the principles of implementation of rights, because it clearly states "to be unconstitutional any act or omission of a regressive nature that diminishes, impair or abolish unjustifiably exercise of rights." In such a way that it is necessary to consider alternatives to channel the right to social security and comprehensive cash in optimal conditions, with objet to strengthen the universalization of the services provided by the IESS, protecting unrestricted rights of members and especially evaluating and planning adequately to meet the institutional coverage efficiently and effectively contingencies required by the population on social security